A Novel Charge-Metering Method for Voltage Mode Neural Stimulation - Luan,S; Constandinou,TG (2012)
This paper presents a novel, fully-integrated circuit for achieving change-balanced voltage-mode neural stimulation based on a charge-metering technique. The proposed system uses two small on-chip capacitors, a counter, two comparators and a control-logic circuit to measure the charge delivered to the tissue. The circuit has been designed to deliver a maximum charge of 10.24nC to the tissue within 100us. It is shown that the charge delivery error is 0.4-4% with a maximum residual charge of -73pC. Implemented in a standard 0.18um CMOS technology, the total power consumption is 42uW (excluding stimulus).